Validation of a Postoperative Nomogram Predicting Recurrence in Patients with Conventional Clear Cell Renal Cell Carcinoma - Lee, Byron H. (Eur Urol Focus, 2016)
BACKGROUND: Clear cell renal cell carcinoma (RCC) continues to be the most commonly diagnosed subtype and is associated with more aggressive behavior than papillary and chromophobe RCC. Predicting disease recurrence after surgical extirpation is important for counseling and targeting those at high risk for adjuvant therapy clinical trials. OBJECTIVE: To validate a postoperative nomogram predicting 5-yr recurrence-free probability (RFP) for clinically localized clear cell RCC. DESIGN, SETTING, AND PARTICIPANTS: We identified all patients who underwent nephrectomy for clinically localized RCC from 1990 to 2009 at Memorial Sloan Kettering Cancer Center. After excluding patients with bilateral renal masses, familial RCC syndromes, and T3c or T4 tumors due to the limited number, 1642 participants were available for analysis. INTERVENTIONS: Partial or radical nephrectomy. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Disease recurrence was defined as any new tumor after nephrectomy or kidney cancer–specific mortality, whichever occurred first. A postoperative nomogram was used to calculate the predicted 5-yr RFP, and these values were compared with the actual 5-yr RFP. Nomogram performance was evaluated by concordance index and calibration plot. RESULTS AND LIMITATIONS: Median follow-up was 39 mo (interquartile range: 14–79 mo), and disease recurrence was observed in 50 patients. The nomogram concordance index was 0.81. The calibration curve showed that the nomogram underestimated the actual 5-yr RFP. We updated the nomogram by including the entire patient population, which maintained performance and significantly improved calibration. CONCLUSIONS: The updated clear cell RCC postoperative nomogram performed well in the combined cohort. Underestimation of actual 5-yr RFP by the original nomogram may be due to increased surgeon experience and other unknown variables. PATIENT SUMMARY: We updated a valuable prediction tool used for assessing the disease recurrence probability after nephrectomy for clear cell renal cell carcinoma.